Penguatan Pendidikan Tauhid melalui Konten Digital Interaktif untuk Siswa Kelas V SDIT Insan Kamil di Era Media Sosial - Husnaini Rahmi Arrumi (STIKes Ibnu Sina Ajibarang, 2025)
This study explores the reinforcement of monotheism (tauhid) education through interactive digital content for fifth-grade students at SDIT Insan Kamil in the social media era. Using a qualitative case study approach, data were collected via classroom observations, interviews with Islamic education teachers, and analysis of digital learning materials. Findings indicate that interactive digital content, including videos, animations, and educational games, enhanced students' understanding of tauhid, increased engagement, and facilitated self-directed learning beyond school hours. Students demonstrated improved participation in discussions and greater confidence in expressing religious inquiries. However, challenges such as unequal access to technology among students were identified. Recommendations include developing tailored digital content aligned with tauhid principles, providing teacher training in technology integration, and addressing technological disparities through collaborative school-parent efforts. This study highlights the potential of digital tools to make Islamic education more relevant and engaging for digitally immersed students, emphasizing balanced collaboration between technology and teacher guidance.